2011
DOI: 10.1088/1748-9326/6/4/045212
|View full text |Cite
|
Sign up to set email alerts
|

Sources and the flux pattern of dissolved carbon in rivers of the Yenisey basin draining the Central Siberian Plateau

Abstract: Frequent measurements of dissolved organic (DOC) and inorganic (DIC) carbon concentrations in rivers during snowmelt, the entire ice-free season, and winter were made in five large watersheds (15 000-174 000 km 2 ) of the Central Siberian Plateau (Yenisey River basin). These differ in the degree of continuous permafrost coverage, mean annual air temperature, and the proportion of tundra and forest vegetation. With an annual DOC export from the catchment areas of 2.8-4.7 gC m −2 as compared to an annual DIC exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 58 publications
7
90
3
2
Order By: Relevance
“…In these regions, it has been suggested that organic J. E. Vonk et al: Effects of permafrost thaw on Arctic aquatic ecosystems 7137 matter sorption onto newly thawed (due to forest fires) mineral soils may also be important (Petrone et al, 2007). Over geographic gradients, changes in permafrost extent appear to have regionally variable effects on DOC flux from land to water, with decreasing permafrost extent (and presumably increasing contact with deeper soils and groundwater inflows) causing increasing DOC fluxes in organic rich regions, but decreasing DOC fluxes in regions with poorly developed organic horizons (Frey and Smith, 2005;Prokushkin et al, 2011;Tank et al, 2012a). Controlled leaching experiments of soils from the Alaskan and western Canadian Arctic have also found that regardless of temperature and leaching time, only small amounts of DOC are released from permafrostimpacted soils, and that mobilization of OC occurred largely in the POC phase (Guo et al, 2007).…”
Section: Organic Matter Delivery To Aquatic Ecosystemsmentioning
confidence: 99%
“…In these regions, it has been suggested that organic J. E. Vonk et al: Effects of permafrost thaw on Arctic aquatic ecosystems 7137 matter sorption onto newly thawed (due to forest fires) mineral soils may also be important (Petrone et al, 2007). Over geographic gradients, changes in permafrost extent appear to have regionally variable effects on DOC flux from land to water, with decreasing permafrost extent (and presumably increasing contact with deeper soils and groundwater inflows) causing increasing DOC fluxes in organic rich regions, but decreasing DOC fluxes in regions with poorly developed organic horizons (Frey and Smith, 2005;Prokushkin et al, 2011;Tank et al, 2012a). Controlled leaching experiments of soils from the Alaskan and western Canadian Arctic have also found that regardless of temperature and leaching time, only small amounts of DOC are released from permafrostimpacted soils, and that mobilization of OC occurred largely in the POC phase (Guo et al, 2007).…”
Section: Organic Matter Delivery To Aquatic Ecosystemsmentioning
confidence: 99%
“…Lower CMAR values may also be linked to lower Selenga River discharge at this time (Fig. g; Prokushkin et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…DOC and DIC were analyzed using a carbon total analyzer (Shimadzu TOC VSCN) with an uncertainty better than 3 %. The instrument was calibrated for analysis of both form of dissolved carbon in organic-rich, DIC-poor waters (e.g., Prokushkin et al, 2011). The UV absorbance of the filtered samples was measured at 280 nm using a quartz 10 mm cuvette on a Cary-50 spectrophotometer.…”
Section: Analysesmentioning
confidence: 99%
“…Mobilization of dissolved organic and inorganic carbon (DOC and DIC, respectively) and related trace elements (TEs) including metal contaminants and micronutrients from the frozen peat to surface waters and further to the Arctic Ocean is one the major consequences of ongoing permafrost thaw (Tank et al, 2012a(Tank et al, , b, 2016Striegl et al, 2005;Rember and Trefry, 2004;Prokushkin et al, 2011;Mann et al, 2012;Grosse et al, 2016;Holmes et al, 2013). The impact of warming on Arctic and subarctic soil is primarily through the active layer thickness (ALT) rise (Zhang et al, 2005;Akerman and Johannson, 2008) although a number of other phenomena (plant productivity, drainage and hydrological regime change, ground fires, etc.)…”
Section: Introductionmentioning
confidence: 99%